New Insights into the Microbiota of the Svalbard Reindeer Rangifer tarandus platyrhynchus - Zielińska, Sylwia (Front Microbiol, 2016)
Svalbard reindeer (Rangifer tarandus platyrhynchus) is a non-migratory subspecies of reindeer inhabiting the high-arctic archipelago of Svalbard. In contrast to other Rangifer tarandus subspecies, Svalbard reindeer graze exclusively on natural sources of food and have no chance of ingestion of any crops. We report the use of a non-invasive method for analysis of fecal microbiome by means of sequencing the 16S rDNA extracted from the fecal microbiota of R. tarandus platyrhynchus from a small, isolated population in Hornsund, South Spitsbergen National Park. Analyses of all samples showed that 99% of the total reads were represented by Bacteria. Taxonomy-based analysis showed that fecal bacterial communities consisted of 14 phyla. The most abundant phyla across the population were Firmicutes and Bacteroidetes, and those phyla jointly accounted for more than 95% of total bacterial sequences (ranging between 90.14 and 98.19%). Specifically, Firmicutes comprised 56.53% (42.98–63.64%) and Bacteroidetes comprised 39.17% (34.56–47.16%) of the total reads. The remaining 5% of the population reads comprised of Tenericutes, Cyanobacteria, TM7, Actinobacteria, Proteobacteria, Verrucomicrobia, Elusimicrobia, Planctomycetes, Fibrobacteres, Spirochaetes, Chloroflexi, and Deferribacteres. Differences in the fecal bacteria composition between particular reindeer were not statistically significant which may reflect the restricted location and similar diet of all members of the local population.